2014
DOI: 10.1186/s13059-014-0429-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing reveals altered long intergenic non-coding RNAs in lung cancer

Abstract: BackgroundLong intergenic non-coding RNAs (lncRNAs) represent an emerging and under-studied class of transcripts that play a significant role in human cancers. Due to the tissue- and cancer-specific expression patterns observed for many lncRNAs it is believed that they could serve as ideal diagnostic biomarkers. However, until each tumor type is examined more closely, many of these lncRNAs will remain elusive.ResultsHere we characterize the lncRNA landscape in lung cancer using publicly available transcriptome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(74 citation statements)
references
References 56 publications
1
73
0
Order By: Relevance
“…Using a previously described method 18 to comprehensively annotate lncRNAs in AML31 we identified 977 previously unannotated multi-exon lncRNA transcripts (See Table S5 for details). The expression levels of the multi-exon lncRNAs are shown in Figure 4A, which combine the datasets for AML31 and the TCGA AML cohort.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a previously described method 18 to comprehensively annotate lncRNAs in AML31 we identified 977 previously unannotated multi-exon lncRNA transcripts (See Table S5 for details). The expression levels of the multi-exon lncRNAs are shown in Figure 4A, which combine the datasets for AML31 and the TCGA AML cohort.…”
Section: Resultsmentioning
confidence: 99%
“…AML31 RNA-seq samples were used to discover novel expressed transcripts using the same methods in 18 . Sequencing reads were aligned using TopHat2 42 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional validation shows that the most differentially expressed lncRNA across lung subtypes, LCAL1 (lung cancer associated lncRNA 1), contributes to cellular proliferation [46]. Furthermore, siRNA-mediated knockdown of MVIH could inhibit cell growth via regulating MMP-2 and MMP-9 protein expression in NSCLC [47].…”
Section: Roles Of Lncrnas In Lung Cancer Biologymentioning
confidence: 99%
“…In addition, analysis of over 300 additional tumor types identified both lung cancer-specific lncRNAs as well as a subset of lncRNAs that are broadly deregulated in many human cancers [51]. Furthermore, Tseng and co-authors surveyed the Cancer Genome Atlas database, representing more than 15,000 tumors, and showed that 18% of these tumors showed a gain in copy-number of the PVT1-containing 8q24.21 region and that nearly 100% of this subpopulation also showed a MYC copy number increase [47].…”
Section: Lncrnas Disease and Cancermentioning
confidence: 99%